2022
DOI: 10.3390/nu14224722
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Nutrition in Patients with Chronic Kidney Disease and Cachexia

Abstract: Rehabilitation nutrition is a proposed intervention strategy to improve nutritional status and physical function. However, rehabilitation nutrition in patients with cachexia and protein-energy wasting (PEW), which are the main nutrition-related problems in patients with chronic kidney disease (CKD), has not been fully clarified. Therefore, this review aimed to summarize the current evidence and interventions related to rehabilitation nutrition for cachexia and PEW in patients with CKD. CKD is a serious conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Low energy intake results in greater catabolism 28) and worsening nutritional status. Furthermore, conditions such as sarcopenia, frailty, and protein energy wasting frequently occur in patients with CKD, and their effects are exacerbated by low nutrient intake 29,30) . Previous studies have reported that frailty and sarcopenia are associated with cardiovascular 31) and all-cause 32) mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…Low energy intake results in greater catabolism 28) and worsening nutritional status. Furthermore, conditions such as sarcopenia, frailty, and protein energy wasting frequently occur in patients with CKD, and their effects are exacerbated by low nutrient intake 29,30) . Previous studies have reported that frailty and sarcopenia are associated with cardiovascular 31) and all-cause 32) mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, excess urea is converted into ammonia by the urease-positive oral microbiota, decreasing the salivary flow and leading to dry mouth, better known as xerostomia, that is usually observed in ESRD patients [223,224]. The CKD patient often perceives an unpleasant metallic taste following the ingestion of food, which consequently leads to decreased appetite and contributes to poor nutritional intake and protein-energy wasting syndrome [225][226][227].…”
Section: Impaired Oral Health and Ckdmentioning
confidence: 99%
“…Recently, rehabilitation nutrition has emerged as a strategy to overcome nutritional alterations and physical dysfunction [ 61 ]. This strategy includes the evaluation of patients’ nutritional and physical states, the definition of aims, and the simultaneous initiation of the nutritional approach and rehabilitation [ 62 , 63 ]. nutritional management can be founded on the International Classification of Functioning, Disability, and Health (ICF).…”
Section: Recommended Approach and Potential Treatments For Ckd-associ...mentioning
confidence: 99%